Diseño de Neuromicrocurrículos para Carreras de Educación Superior - Mantuano, Marcel Oswaldo Méndez; Robles, Darwin Vicente Apolo; Gómez, Rolando Gastón Viteri; Román, Gladys Johanna Quijije; Vargas, Marlene Jacqueline Cortez; Flores, Jennifer Lisenya Mantuano (European Scientific Journal, ESJ, 2019)
Although risky and potentially soft, the current exploration links two sciences that are not fully addressed, neurosciences and education sciences; with the purpose that the research serves as a reference to design the fundamental structure of the components that a neuromicrocurriculum must possess. The presented proposal of the pedagogical design, emphasizes the emotions that are involved in the normal processes of teaching and learning, to determine which should be enhanced by the educational methodologies that are embodied in the microcurricula. The need to establish curricular contents that develop the neurological biological aspects is determined, to link the knowledge with emotional aspects, in such a way that the learning dynamizes the cerebral plasticity to model substantive knowledge in the long term memory of the students. The research has a qualitative approach, with a documentary design and a descriptive scope. Aunque arriesgada y potencialmente blanda, la actual exploración enlaza a dos ciencias poco abordadas de forma integral como son las neurociencias y las ciencias de la educación, esto con el propósito de que la investigación sirva como referencia para diseñar la estructura fundamental de los componentes que debe poseer un neuromicrocurrículo. La propuesta presentada del diseño pedagógico hace énfasis en las emociones que se encuentran involucradas en los procesos normales de enseñanza y aprendizaje, para determinar cuáles deberían ser potenciadas por las metodologías educativas que se encuentran plasmadas en los microcurrículos. De igual forma se determina la necesidad de establecer contenidos curriculares que desarrollen los aspectos biológicos neuronales para enlazar los conocimientos con aspectos emocionales, de tal forma, que el aprendizaje dinamice la plasticidad cerebral para modelar conocimientos sustantivos en la memoria a largo plazo de los estudiantes. La investigación tiene un enfoque cualitativo, con un diseño documental y un alcance descriptivo.